PENGARUH LINGKUNGAN KAMPUS DAN TEMAN SEBAYA TERHADAP KEDISIPLINAN HAFALAN TAHFIZ MAHASISWA - Destia Vani; Fitriyani; Chelsea Andreana Natasha; Edi Hermanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Discipline in memorizing the Quran (tahfiz) is one of the most crucial factors that determine a student's success in completing a memorization program. Many students possess a good foundational memorization ability, yet fail to maintain consistency due to a lack of environmental support and community. This study aims to examine the extent to which campus environment and peer influence affect students' tahfiz memorization discipline. The method used is library research with a descriptive-analytical approach. Data were collected from various journals, books, and relevant prior studies, then systematically analyzed. The results indicate that a conducive campus environment — encompassing facilities, tahfiz program policies, academic culture, and the role of supervising lecturers — has a significant positive influence on students' memorization discipline. Likewise, the presence of supportive peers who share a high enthusiasm for memorization has been proven to strengthen individual commitment and motivation in maintaining memorization routines. This article concludes that the synergy between these two factors is the primary key to establishing a healthy and sustainable tahfiz culture in higher education institutions.